Without capacity, there is no development - De Grauwe, Antonde (Rethinking capacity development., 2009)
"IIEP/UNESCO undertook a wide range of studies to analyze the record of capacity development and to propose innovative and relevant policies and strategies."--www.ieep.unesco.org.